THE ANALYSIS OF COMPANY CHARACTERISTIC INFLUENCE TOWARD CSR DISCLOSURE: EMPIRICAL EVIDENCE OF MANUFACTURING COMPANIES LISTED IN JSX - Arief Rahman; Kurnia Nur Widyasari (Jurnal Akuntansi dan Auditing Indonesia, 2008)
This paper investigates the influence of company characteristic toward Corporate Social Responsibility disclosure. The research is using the proxy of management ownership, leverage, size, profitability and company profile as the variable of company characteristic, while the CSR disclosure, unlike the previous researches, is proxied by dummy score from the companies’ mandatory disclosure based on the items of Public Environmental Reporting Initiative (PERI) and Global Reporting Initiative Social Performance (GRISP) issued by Global Reporting Initiative (GRI). Our research found that simultaneously, company characteristics significantly influence CSR disclosure. Whereas based on the partial test, amongst the characteristics observed, only company profile which significantly influences CSR disclosure. The result indicates that legitimacy from the society is the big concern of companies and therefore drives the actions of companies. However, the disclosure presumably depends on the awareness of the management toward social and environmental prosperity because the pressure from investors and market is still weak. Keywords: Corporate Social Responsibility, management ownership, leverage, size, profitability, company profile